THE ROMAN POTTERY CENTRES OF URMITZ AND MAYEN (DISTRICT MAYEN-KOBLENZ, GERMANY): New archaeological and typological evidence for dating their production and the usage of their products - Kiessel , Marko (Rei Cretariae Romanae Fautorum Acta, 2024)
The common-ware potteries of Urmitz/Weissenthurm were situated in the Middle-Rhine/Mosel-region, close to the city of Koblenz in the western German federal state Rheinland-Pfalz, in the ancient province Germania superior. The state of research on the pottery centre, which extended across the meadow “Am guten Mann” between the municipalities of Urmitz und Weissenthurm in the so-called Neuwieder valley, is moderate: known since the 19th century, no intensive excavations were undertaken before those of the 1970s by Hans Eiden (OELMANN 1914, 70; UNVERZAGT 1916, 32; STAMM 1962, 91; EIDEN 1982, 175–195). Since then the numerous discoveries await a complete scholarly analysis. Characteristic for Urmitz coarse ware is a whitish, yellowish or beige-coloured fabric which is moderately textured and of slaty pattern, containing fine, often red quartz sand. The colour of the sherd’s surface varies from grey, grey-blue, yellowish-beige to yellowish-green (OELMANN 1914, 70; STAMM 1962, 91–92).